2011
DOI: 10.1002/app.33767
|View full text |Cite
|
Sign up to set email alerts
|

Flame‐retardant synergism of sepiolite and magnesium hydroxide in a linear low‐density polyethylene composite

Abstract: A synergistic effect on flame retardancy, thermal stability, and mechanical properties was found when sepiolite was incorporated into a linear low-density polyethylene (LLDPE)/magnesium hydroxide (MH) composite. Different amounts of sepiolite (up to a maximum concentration of 15 phr) were added to a standard LLDPE/MH formulation, and vinyltriethoxysilane was used as a compatibilizer as well as a crosslinking agent. The thermal stability and the oxidation induction time increased with increasing sepiolite conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 21 publications
2
46
0
Order By: Relevance
“…These phenomena depend primarily on homogeneous filler dispersion. For the material modified with maleic anhydride, PP/10% PP-g-MAH/30% Mg(OH) 2 , the rate reduction from 24.3 mm min -1 to 14.1 mm min -1 and the 42% decrease compared to pure polypropylene are significant compared with literature data [11][12][13]37].…”
Section: Flame Retardant and Thermal Properties Of Pp/mg(oh) 2 Composmentioning
confidence: 56%
See 4 more Smart Citations
“…These phenomena depend primarily on homogeneous filler dispersion. For the material modified with maleic anhydride, PP/10% PP-g-MAH/30% Mg(OH) 2 , the rate reduction from 24.3 mm min -1 to 14.1 mm min -1 and the 42% decrease compared to pure polypropylene are significant compared with literature data [11][12][13]37].…”
Section: Flame Retardant and Thermal Properties Of Pp/mg(oh) 2 Composmentioning
confidence: 56%
“…Mg(OH) 2 silanization using 3-aminopropyltriethoxysilane produced unfavorable results: there was an increase in the Young's modulus but a fall in the values of the other mechanical parameters, including by 40% for elongation at break. Gul et al [13] also observed a dramatic fall in this parameter (from 111.6% to 1.3%). Such unfavourable results are comparable to those obtained here (Table 2) and indicate brittleness.…”
Section: Mechanical Properties Of Pp/mg(oh) 2 Compositesmentioning
confidence: 85%
See 3 more Smart Citations